HGG-18. MOLECULAR PATHOPHYSIOLOGY OF HISTONE G34R MUTANT CHILDHOOD BRAIN TUMOURS; TOWARDS THE DEVELOPMENT OF NOVEL TARGETED THERAPIES. Issue 2 (22nd June 2018) - Haque, Farhana; Lourdusamy, Anbarasu; Rahman, Ruman; Varlet, Pascale; Carcaboso, Angel; Jones, Chris; Layfield, Robert; Grundy, Richard
Abstract: There have been no recent improvements in the treatments for childhood and adolescent High-Grade Glioma (pHGG) and Diffuse Intrinsic Pontine Glioblastoma (DIPG) which continue to have a very poor prognosis (<25%). These cancers are defined by mutations affecting histone 3 proteins, indeed 80% of DIPGs harbour histone H3.1 and H3.3 K27M somatic mutations whilst 30% of pHGGs exhibit H3.3 G34R or G34V mutations. Several studies have highlighted the epigenetic changes associated with these mutations, however their precise role in tumourigenesis is still unknown. We have generated and validated a Histone 3.3 (H3.3) G34R antibody and investigated the downstream effects of H3.3 G34R mutations in pHGG. In order to identify the genes that may be deregulated by mutant histone expression, we have performed chromatin immunoprecipitation (ChIP) assays with our H3.3 G34R and wild type H3 antibodies, using pHGG mutant and wild type cell lines. Initial analyses of ChIP data have implicated deregulation of various cell signaling pathways including as Notch, Hedgehog, PAR-1, PLC-beta and Androgen, in H3 G34R mutated pHGG. Specifically, Notch pathway genes e.g. HES1/HES5 were found enriched at promoter regions by the H3.3 G34R antibody in mutant cell lines. We are currently determining the effects of altered expression or inhibition of Notch pathway components on tumorigenesis of H3 G34R mutated pHGG, through protein/gene expression and inhibition assays. These analyses should enable us to find potential novel therapeutic targets. Results of these initial analyses/experiments will be presented.